Internalisasi soft skills dan minat kewirausahaan dalam pembentukan jiwa kewirausahaan: - Putri Yunita Aprillianita; Eeng Ahman; Kodri Kodri (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This study aims to determine and analyze the effect of internalization of soft skills and entrepreneurial interest in the formation of the entrepreneurial spirit of students in MAN in Kuningan Regency. The method used in this study is an explanatory survey method with data collection techniques through distributing questionnaires to students of MAN in Kuningan Regency. The research instrument used has been tested for validity and reliability. The population of this research is all students of MAN in Kuningan Regency as many as 2,123 students, while based on Slovin calculation, the sample is 355 students. The collected data were then analyzed using descriptive analysis techniques and multiple linear regression. The results showed that: 1) the level of internalization of soft skills, entrepreneurial interest and entrepreneurial spirit of students were in the high category. 2) internalization of soft skills has an effect on the formation of an entrepreneurial spirit. 3) interest in entrepreneurship affects the formation of an entrepreneurial spirit. 4) internationalization of soft skills and entrepreneurial interest have an effect on the formation of an entrepreneurial spirit. These findings indicate that to form an entrepreneurial spirit, it is necessary to increase the internalization of soft skills and interest in entrepreneurship.